Swim team - Christmas, Johnnie (Harper Alley, 2022)
Bree is looking forward to her first day at her new middle school, Enith Brigitha, home of the Mighty Manatees, but she's disappointed when the only elective that fits into her schedule is Swim 101. Swimming is one of her greatest fears, and she's less than enthusiastic about diving in, especially at a school that is deeply invested in its swim team. Luckily, Etta, an elderly neighbor in her apartment building and former swim team captain, is happy to help Bree, and she's surprised to suddenly find herself on the school's swim team thanks to her newfound water skills. As Bree makes friends on the team, she must deal with the town's expectations and help the Manatees beat their rival, the prestigious Holyoke Prep.